2019
DOI: 10.1097/qad.0000000000002212
|View full text |Cite
|
Sign up to set email alerts
|

HIV stigma and viral load among African-American women receiving treatment for HIV

Abstract: Objective: African-American women are more likely than other women in the United States to experience poor HIV-related health; HIV stigma may contribute to these outcomes. This study assessed the relationship between HIV stigma and viral load, over time, among a sample of African-American women receiving treatment for HIV, and explored social support and depressive symptoms as mediators. Design: Secondary analysis of longitudinal data. Methods: Data came from a randomized trial of an intervention to reduce HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 58 publications
3
42
1
1
Order By: Relevance
“…This followed a smaller study in the United States nested within a randomized trial of an intervention to reduce HIV stigma among 234 African American women in HIV care in 3 cities, in which changes in viral load over time were associated with experiences of stigma. 19 In another US study, among 92 young Black men who have sex with men, those who reported higher levels of total stigma and personalized stigma were less likely to be virally suppressed. 21 These studies build on a wealth of evidence from multiple settings that suggest that stigma is a barrier to the continuum of care for PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…This followed a smaller study in the United States nested within a randomized trial of an intervention to reduce HIV stigma among 234 African American women in HIV care in 3 cities, in which changes in viral load over time were associated with experiences of stigma. 19 In another US study, among 92 young Black men who have sex with men, those who reported higher levels of total stigma and personalized stigma were less likely to be virally suppressed. 21 These studies build on a wealth of evidence from multiple settings that suggest that stigma is a barrier to the continuum of care for PLHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence continues to grow of the negative relationship of stigma to pre‐exposure prophylaxis [1], HIV testing [2‐4], linkage and retention in care [5‐7], medication adherence [8‐13] and viral load suppression [2,14,15]. More visible global recognition of stigma in fuelling the HIV epidemic and in undermining the HIV response has been forthcoming through recent global declarations [29,35,71].…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for addressing stigma for an effective HIV response and to achieve national and global targets is clearly underscored by the evidence of the negative link between stigma and testing [2,3], treatment [10‐13] and viral load suppression [2,14,15]. The importance and urgency of responding to stigma in a consistent and scaled manner is visible in recent global calls for stigma‐reduction initiatives [29,35,71,72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In longitudinal analyses, the direct association between higher HIV stigma and lower odds of VL suppression persisted, while the hypothesized mediators of this association (depressive symptoms and social support) remained nonsignificant. 46 Taken together, these intriguing findings suggest an inverse relationship between HIV stigma and HIV-related health—wherein higher degrees of subjective experiences of HIV-related stigma directly associate with objective measures of HIV VL. However, the potential psychosocial and behavioral mediators of this emergent association remain unclear, and to date, the possibility of a direct relationship between HIV stigma and HIV-related health outcomes has yet to be examined in a sample of OALWH.…”
Section: Introductionmentioning
confidence: 93%